1979
DOI: 10.1351/pac197951040831
|View full text |Cite
|
Sign up to set email alerts
|

Hormone-receptor interactions: a study of the binding of hormone-substituted tobacco mosaic virus to membrane vesicles by dynamic light scattering and by transient electric bi-refringence

Abstract: -Tobacco mosaic virus has been covalently conjugated with 500 -600 molecules of different hormones. The particles react with antisera against the hormones and with hormone receptors in target organs, on target cells, and on membrane vesicles. The compounds were used for cooperative affinity labelling and for the isolation of receptor-bearing vesicles. The binding of a tobacco mosaic virus/angiotensin II conjugate to adrenal cortex membrane vesicles was studied by dynamic light scattering and transient electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The third model of protein interaction involves a natively unstructured protein that folds upon interaction with another partner. This was proposed for peptide hormones in the 1970s by Robert Schwyzer ( Schwyzer et al., 1979 ) and experimentally exemplified by X-ray analysis and NMR studies of glucagon in the Blundell and Wüttrich labs ( Braun et al., 1983 , Sasaki et al., 1975 ) suggesting a disorder-to-order transition on receptor binding from glucagon with a single turn of helix in solution by NMR ( Braun et al, 1983 ) to one with a much longer region defined by X-ray analysis in the trimer ( Sasaki et al, 1975 ) and at lipid interfaces ( Braun et al, 1983 ) and proposed at the receptor ( Blundell, 1979 , Blundell and Wood, 1982 ). Subsequently, Wright & Dyson ( Wright and Dyson, 1999 , Wright and Dyson, 2009 ) showed that such concerted folding and binding involving peptides or disordered regions of polypeptide chains is actually widespread in intracellular regulatory systems.…”
Section: Flexibility In Partner Interactionsmentioning
confidence: 97%
“…The third model of protein interaction involves a natively unstructured protein that folds upon interaction with another partner. This was proposed for peptide hormones in the 1970s by Robert Schwyzer ( Schwyzer et al., 1979 ) and experimentally exemplified by X-ray analysis and NMR studies of glucagon in the Blundell and Wüttrich labs ( Braun et al., 1983 , Sasaki et al., 1975 ) suggesting a disorder-to-order transition on receptor binding from glucagon with a single turn of helix in solution by NMR ( Braun et al, 1983 ) to one with a much longer region defined by X-ray analysis in the trimer ( Sasaki et al, 1975 ) and at lipid interfaces ( Braun et al, 1983 ) and proposed at the receptor ( Blundell, 1979 , Blundell and Wood, 1982 ). Subsequently, Wright & Dyson ( Wright and Dyson, 1999 , Wright and Dyson, 2009 ) showed that such concerted folding and binding involving peptides or disordered regions of polypeptide chains is actually widespread in intracellular regulatory systems.…”
Section: Flexibility In Partner Interactionsmentioning
confidence: 97%
“…Many of the latter group involve flexible polypeptides or disordered regions of polypeptide chains that assemble with a more classical globular protein to give a globular complex (Wright & Dyson, 1999, 2009). Schwyzer proposed this idea for polypeptide hormones in the 1970s (Schwyzer et al 1979). It was exemplified by glucagon where biophysical and X-ray analyses (Sasaki et al 1975) together with NMR studies in a lipid–water interface (Braun et al 1983) suggested a disorder-to-order transition of the polypeptide on receptor binding (Blundell, 1979; Blundell & Wood, 1982).…”
Section: Ppis and Their Chemical Modulatorsmentioning
confidence: 99%